2018
DOI: 10.1016/j.jid.2018.03.400
|View full text |Cite
|
Sign up to set email alerts
|

393 A trial to determine the effect of psoriasis treatment (adalimumab, phototherapy, and placebo) on cardiometabolic disease: The vascular inflammation in psoriasis (VIP) trial

Abstract: Psoriasis is a common chronic inflammatory skin disease, affecting 2-4% of world population. MicroRNAs (miRNAs) are short non-coding RNAs that regulate expression of the majority of protein-coding genes. In psoriasis, previous studies have identified deregulation in miRNA expression. Most of these studies utilized full-depth skin biopsies and thus may have missed the cell-specific miRNomic signature. Here, we analyzed the miRNome of CD45 neg sorted epidermal cells from psoriasis patients and healthy skin by ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 0 publications
0
9
0
Order By: Relevance
“…Eighty-three RCTs (reported in 127 articles) were included in the SR and 77 (including 34,816 patients) in the NMA. The trials not included in the NMA did not provide results at all [5557] or in an appropriate format [58], or included a comparator that would not connect relevant interventions in the network [59, 60].…”
Section: Resultsmentioning
confidence: 99%
“…Eighty-three RCTs (reported in 127 articles) were included in the SR and 77 (including 34,816 patients) in the NMA. The trials not included in the NMA did not provide results at all [5557] or in an appropriate format [58], or included a comparator that would not connect relevant interventions in the network [59, 60].…”
Section: Resultsmentioning
confidence: 99%
“…As such, the emerging field of biologic treatments is exciting as it may provide therapeutic utility in psoriasis with added benefits of modulating CVD risk. Furthermore, completed and ongoing trials assessing the subclinical CVD in psoriasis have demonstrated promising findings ( 143 , 144 ).…”
Section: Future Directionsmentioning
confidence: 99%
“…However, the study does add to a growing literature of observational studies in rheumatoid arthritis and psoriasis suggesting that TNFi are associated with a reduction in CV events 5 . In contrast, two recent, well powered RCTs demonstrated no benefit of TNFi on aortic vascular inflammation, however, important inflammatory CV risk biomarkers such as CRP and GlycA were strongly improved providing some experimental evidence of the potential benefit of TNFi on CV events 6, 7 . Critically, a recent randomized placebo controlled trial (CANTOS) of canakinumab, a biologic targeting Il-1 beta, in 10,061 patients with prior MI and elevated CRP demonstrated, for the first time, that immune targeted treatment causes a reduction in major CV events.…”
mentioning
confidence: 90%